Climate Change Induced Landslide Susceptibility Assessment - for Aiding Climate Resilient Planning for Road Infrastructure: A Case Study in Rangamati District, Chittagong Hill Tracts, Bangladesh. Issue 1 (1st November 2022) - Wijaya, I P K; Joshi, A; Alam, M N; Jayasinghe, S; Laila, N
Abstract : Climate change induced extreme hydro-meteorological conditions have increased the prevalence of landslides in the hilly and geologically fragile region of Chittagong Hill Tract districts (including Rangamati) in Bangladesh. These landslides have attributed to significant damages to transportation infrastructures such as roads and bridge. In this study, we investigated the susceptibility of landslides due to extreme rainfall events under different climate change scenarios in Rangamati district. We developed high-resolution 1km x 1km downscaled extreme rainfall projections under RCP 4.5 and RCP 8.5 scenarios for baseline period 1976-2005 and for future time horizons 2030s, 2050s, and 2080s. Based on these extreme rainfall scenarios, the combination of the Frequency Ratio (FR) and Analytical Hierarchy Process (AHP) techniques were applied to map and analyse the landslide susceptibility maps. Nine multi-variate factors contributing to the landslides were considered including terrain slope, aspect, elevation, lithology, soil, distance from the lineaments, distance from the stream, land use and mean annual rainfall in four different time periods for scenario RCPs. Further, an Area Under the Curve (AUC) approach was used to evaluate the quality of the model A total of seven landslide susceptibility maps were developed and classified into five susceptible classes. The models were validated using the Receiver Operating Characteristic curve (ROC) approach, which showed a satisfactory result of 80-86 percent accuracy.